Determination of the lipophilicity of Salvia miltiorrhiza Radix et Rhizoma (danshen root) ingredients by microemulsion liquid chromatography: optimization using cluster analysis and a linear solvation energy relationship‐based method. (24th November 2015) - Li, Liangxing; Yang, Jianrui; Huang, Hongzhang; Xu, Liyuan; Gao, Chongkai; Li, Ning
Abstract: We evaluated 26 microemulsion liquid chromatography (MELC) systems for their potential as high‐throughput screening platforms capable of modeling the partitioning behaviors of drug compounds in an n‐ octanol–water system, and for predicting the lipophilicity of those compounds (i.e. log P values). The MELC systems were compared by cluster analysis and a linear solvation energy relationship (LSER)‐based method, and the optimal system was identified by comparing their Euclidean distances with the LSER coefficients. The most effective MELC system had a mobile phase consisting of 6.0% (w/w) Brij35 (a detergent), 6.6% (w/w) butanol, 0.8% (w/w) cyclohexane, 86.6% (w/w) buffer solution and 8 mm cetyltrimethyl ammonium bromide. The reliability of the established platform was confirmed by the agreement between the experimental data and the predicted values. The log P values of the ingredients of danshen root ( Salvia miltiorrhiza Radix et Rhizoma) were then predicted. Copyright © 2015 John Wiley & Sons, Ltd.